Regional variability of modified Ferriman-Gallwey scorring in premenopausal healthy women in Southern Turkey. (3rd August 2022) - Vural Solak, Gurgun Tugce; Akkus, Gamze; Solak, Yavuzalp; Kose, Sevgul; Sert, Murat
Abstract: Objective Although modified Ferriman-Gallwey (mF-G) scorring has been the gold standard for assessing hirsutism, also known that this scorring could show variability according to ethnicity. Hence, false positive hirsutism diagnosis and unnecessary anti-androgen therapy can prescribed. It was aimed to disclose the regional characteristics of this scorring in healthy women living in Southern Turkey. Methods 360 women between 18 and 50 years of age were randomly screened. Their medical history, including ovulation periods, gestation(s), family history, known drug use was obtained. Physical examination with mF-G scoring and serum hormone measurements were performed. Women with hirsutism who scored ≥ 8 were further investigated for any underlying disease or cause of hirsutism. After these investigations, the women were divided into three groups according to the mF- G ≥ 8 score and evaluated. Group A ( n = 59) had an mF- G ≥ 8 and, revealed an underlying disease causing hirsutism; group B ( n = 42) had an mF- G ≥ 8, but no underlying disease responsible for hirsutism; and the third group (Group C, n = 259) had an mF- G ≤ 8 and thus, no signs of hirsutism. Results The mean mF-G scores of three groups were 12.78 ± 4.4, 11.48 ± 4.6, and 5.53 ± 3.4, respectively. Of the 59 (16.1%) women in Group A, 46 (44.2%) were diagnosed as polycystic ovary syndrome (PCOS), 8 (7.7%) had idiopathic hyperandrogenism, 7 (6.7%) had nonclassic congenital adrenal hyperplasia, and 1 (1%) had a prolactinoma. When compared to group B, group A women had significantly decreased fertility ( p = .001) and menstrual irregularities ( p = .001). Conclusions In this study, results revealed a significant rate of healthy women (11.6%) who had an mF- G ≥ 8, but no underlying disease causing hirsutism yet were considered hirsute according to their mF-G cutoff. Also, the majority of the studied women (71.9%) living in Southern Turkey were found to have a hair-pattern similar to the European Women. Therefore, we suggest that regional and ethnical body-hair patterns should be considered before prescribing anti-androgen therapy.